Investigating the impact of online language exchanges on second language speaking and willingness to communicate of Chinese EFL learners: a mixed methods study - Zhou, Anju (Frontiers in Psychology, 2023)
The current research investigates the impact of online language exchanges on the speaking skills and willingness to communicate (WTC) of 58 Chinese postgraduate students enrolled in a second-year advanced English program. Participants were divided into two intact classes: e-tandem and conventional, with the former using the Tandem language exchange application to communicate with foreign English speakers online and the latter participating in collaborative speaking tasks inside the class. The IELTS speaking module, WTC scale, and semi-structured interviews were carried out to collect the data. The findings reveal that both groups improved their speaking skills and WTC, but the group who used online language exchanges outperformed the conventional group. The EFL learners also had positive attitudes and perceptions towards the online language exchanges, although some expressed reservations. The study concludes with pedagogical implications for collaborative speaking courses in EFL settings.